Criterion Validity and Test-Retest Reliability of a Modified Version of the International Physical Activity Questionnaire–Short Form (IPAQ-SF) in Kidney Transplant Recipients - Kohlbrenner, Dario; von Moos, Seraina; Schmid-Mohler, Gabriela (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Accelerometry, the clinically valued standard of physical activity monitoring, has limited acceptance in transplantation rehabilitation; therefore, the International Physical Activity Questionnaire (IPAQ) self-report instrument is widely used. However, while the IPAQ’s repeatability is good, its criterion validity is unsatisfactory. We hypothesized that adding a concise oral introduction would help overcome this shortfall. Materials and Methods: This is a secondary analysis of a RCT in a sample of kidney transplant recipients that underwent observational follow-up. We assessed criterion validity of our modified version of the four-item IPAQ–Short Form (mIPAQ–SF) via Pearson, and test-retest reliability via intraclass correlation coefficients. The main difference in the new version is an oral pre-measurement introduction to the questionnaire’s concepts. We compared our results with those of published studies. Results: Post-kidney-transplantation data of 92 patients were analysed. Across the four IPAQ/mIPAQ–SF items, values of correlations between mIPAQ-SF responses and accelerometry records ranged from 0.07 (minutes in vigorous activity) to 0.35 (minutes in moderate activity) for criterion validity, and from 0.19 (days with moderate activity) to 0.58 (minutes in moderate activity) for test-retest reliability. Discussion: Regarding moderate-to-vigorous physical activity, mIPAQ-SF self-reports’ correlations to accelerometry records improved considerably on those of the IPAQ (r=0.18 versus r=0.33), i.e., improved criterion validity. We therefore conclude that a pre-measurement oral explanation of key IPAQ/mIPAQ concepts enhances criterion validity regarding self-reported moderate-to-vigorous physical activity.